An Abundance of Doctoral Students But a Scarcity of Doctorates - Kwiek, Marek (My University, 2020)
The massification of doctoral studies in Poland has not led to an equivalent increase in doctoral degrees. While the number of doctoral students increased steadily through the 1990s and 2000s, the number of doctorates awarded did not follow suit. Many students entered doctoral programs, but only a minority were ever awarded the degree, as most either dropped out or completed the program but did not defend their dissertation. This disparity between entrants and doctoral degrees awarded is central to understanding the emergent tensions around doctoral education in the Polish context. Based on international comparative statistics, the current intake of 43,000 doctoral students combines overproduction of doctoral students and a scarcity of doctorates. In the Polish context, only one in four doctoral students are ultimately awarded a doctoral degree. It follows that the processes affecting the distribution of doctoral education differ from those that determine the distribution of doctorates. The emergent tensions reveal the fundamental difference between the changing higher education system in terms of teaching (where the Bologna Process places doctoral education) and research (where doctorates awarded belong). In Poland, there is the further difference of national statistics, as fields of study used to report doctoral student numbers differ from those used to report doctorates awarded. What has changed fundamentally during this time, however, is the gender composition of doctorate holders, with a gradually increasing share of female doctorates. While 31% of doctorates in 1990 were awarded to females, the percentage rose after a decade of change—to 42% in 2000, and to 53% by 2010. From a gender perspective, the turning point was 2008 when, for the first time in the history of Polish science, the number of female doctorates exceeded the number of male doctorates. Currently, reforms are accelerating and the expectation is that public funding for both higher education and for academic research will be higher. In the center of the reform package there is a concept of competition: between research teams, academic units and institutions, with a new model of academic research assessment to be applied in 2021. The concept includes also new doctoral schools competing for public subsidies and top minds.
Keywords: doctoral education; Polish higher education; massification; PhD students; doctoral schools; Polish universities